Gendered pathways from school to work: The association between field of study and non-standard employment outcomes in Canada. (December 2018) - Pullman, Ashley
Abstract: Women are often over-represented in non-standard employment, such as part-time and temporary work. Lesser known is if post-secondary fields of study foster or attenuate this form of employment inequality. To understand this mechanism, the following study considers the extent to which academic disciplines propagate gender inequality in part-time and temporary employment among recent graduates in Canada. To fully understand the strength of the association between field of study and temporary and part-time work, this article compares other educational, demographic and employment factors as alternative explanations for early-career non-standard employment. The results demonstrate that rates of non-standard employment not only vary substantially by field of study, but the over- and under-representation of women in certain disciplines is a main factor explaining gender differences in early career part-time and temporary employment.